2023
DOI: 10.1051/0004-6361/202346216
|View full text |Cite
|
Sign up to set email alerts
|

ExoMDN: Rapid characterization of exoplanet interior structures with mixture density networks

Abstract: Aims. Characterizing the interior structure of exoplanets is essential for understanding their diversity, formation, and evolution. As the interior of exoplanets is inaccessible to observations, an inverse problem must be solved, where numerical structure models need to conform to observable parameters such as mass and radius. This is a highly degenerate problem whose solution often relies on computationally expensive and time-consuming inference methods such as Markov chain Monte Carlo. Methods. We present Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Valencia et al 2007). Recent studies with more advanced interior models, allowing for additional phases and internal layers in the interior, confirmed these requirements on radius and mass precision when constraining the planets interior structure (Otegi et al, 2020;Dorn and Lichtenberg, 2021;Baumeister and Tosi, 2023).…”
Section: Brief Summary Of State Of the Artmentioning
confidence: 84%
See 2 more Smart Citations
“…Valencia et al 2007). Recent studies with more advanced interior models, allowing for additional phases and internal layers in the interior, confirmed these requirements on radius and mass precision when constraining the planets interior structure (Otegi et al, 2020;Dorn and Lichtenberg, 2021;Baumeister and Tosi, 2023).…”
Section: Brief Summary Of State Of the Artmentioning
confidence: 84%
“…The planetary bulk composition and evolving interior structure are also important for assessing the possible evolutionary pathways of such planets (especially for low-mass, rocky planets) and their surface processes. Studies focusing on Earth-like compositions have already shown that key processes such as plate tectonics, volcanic activity or magnetic field generation (all directly linked also to the atmospheric evolution) strongly depend on planetary mass, metallic core size and surface temperature (Wagner et al, 2011(Wagner et al, , 2012Valencia et al, 2007;Kite et al, 2009;Ortenzi et al, 2020;Dorn et al, 2018;Bonati et al, 2021;Kislyakova and Noack, 2020;Baumeister and Tosi, 2023). The atmospheric evolution is further influenced by the orbital distance of the planets, another observable of PLATO, leading to a bifurcation in atmospheric evolution (Hamano et al, 2013) and erosion efficiency (Godolt et al, 2019;Moore and Cowan, 2020), which can furthermore influence the measured planetary radius.…”
Section: Brief Summary Of State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…We then feed each of them through the well-trained MDN model, yielding the predicted probability distributions of the output variables. Recently it has been suggested by Baumeister & Tosi (2023) that resampling from the predicted distributions and then merging these samples can reduce memory usage and improve computational efficiency. In this work, we experimented with this approach and found it to be markedly less demanding on memory and processing resources.…”
Section: Comparison Between Mdns and Mcmc For Representative Rocky Ex...mentioning
confidence: 99%
“…Based on this, Zhao & Ni (2021 expanded the MDN framework to simultaneously predict layer thicknesses and core properties for a wide range of planets, including Earth-like planets and gas giants. Baumeister & Tosi (2023) developed an ML model, ExoMDN, for predicting the thickness of various layers and mass distributions, based on observed parameters such as mass, radius, equilibrium temperature, and tidal Love number k 2 . The evolution of ML applications in planetary science highlights its potential to accelerate our understanding of the interiors of exoplanets.…”
Section: Introductionmentioning
confidence: 99%